How to stabilize large soluble (hetero-)acenes - Freudenberg, Jan; Bunz, Uwe H. F. (Journal of the American Chemical Society, 2024)
The higher acenes and azaacenes (>(aza)heptacenes) are fascinating, yet elusive materials. Their reactivity and sensitivity increases concomitantly with their size. In recent years, confinement techniques, that is isolation of acenes in matrices and on surfaces, has surpassed solution-based chemistry with respect to accessing the larger (hetero)acenes at the price of the accessibility of no more than a couple thousands of molecules. Isolating acenes in bulk quantities and in processable form is vital for applications in organic electronics as well as from a viewpoint from basic research. In this Perspective, we will discuss after a short historical outline their degradation pathways, and then will selectively highlight recent efforts in stabilizing soluble (aza)acenes.
Online veröffentlicht: 11. Juni 2024
Gesehen am 14.11.2024